Senior Schools Biology Teachers ‘Views on Entrepreneurial Opportunities in Ilorin, Kwara State - ALABI, Hafsat Imam (Ilorin Journal of Education, 2025)
The turnout rate of biology education graduates is alarming, leading to saturated labour market and widespread unemployment. This lack of alignment between capital and nature, result to poverty. Incorporating entrepreneurship opportunities in to biology could assist in ameliorating poverty. Hence, the need to understand teachers' viewpoints, as curriculum implementers, on bio entrepreneurial opportunities. This study explored multi-stage sampling, selecting 23 schools from Ilorin West Local Government area through random sampling. All biology teachers from these schools were purposively sampled having established their consent to be part of the project. A researcher developed questionnaire entitled Biology Teacher’s View on Bio Entrepreneurship Opportunities was used for data collection; the reliability value of 0.85 was obtained using Cronbach alpha, and Chi-square statistic was used to test the hypotheses at a 0.05 level of significance. Outcomes showed that teachers held positive views towards bio entrepreneurship, though no significant difference between private and public-school teachers; and among teachers with varying qualifications. The study concluded that furthering biology teachers' entrepreneurial skills could facilitate graduate employment and wealth creation. Government and school proprietors were recommended to establish periodic seminars to educate and equip teachers with bio-entrepreneurial skills. Moreover, establishing bio entrepreneurship clubs in schools as extracurricular activities will offer practical training to students, prepare them for post-graduation employment, and encourage economic self-sustainability. These initiatives will assist in alleviating unemployment and fostering a viable economy.